An Empirical Evaluation on Value Chain Operations Performed in Marketing of Marine Fisheries in Andhra Pradesh - Devi Prasad Kotni, V. V. (Prabandhan: Indian Journal of Management, 2019)
The study has been designed to capture the core of the flow and processes of the value chain in the marine fisheries sector of Andhra Pradesh. The framework of the study will aid in understanding the different levels of the value chain-its function and significance, the cost of operations, etc. This is a comprehensive study on various value chain actors and their role in value chain management of fisheries in relation to various markets. The main aim of the study was to identify various value chain operations performed by fishermen, exporters, and retailers and to know the various operational costs involved at each stage of fish catch, its processing, and selling. The study illustrated four types of value chains in marine fisheries of Andhra Pradesh, that is, exporter value chain, fresh fish value chain, dry fish value chain, and retailer value chain.